Infusion, Diffusion, and Acculturation on Instructional Training: Lived Experiences of Social Studies Teachers - Monloy, Lea; Espacio, Nancy (JPAIR Multidisciplinary Research, 2025)
Teaching Social Studies is more than just delivering lessons, it’s about shaping perspectives, and encouraging critical thinking. Hence, this exploration was triggered to hear directly from Social Studies teachers about their real-life experiences with instructional training. The study explores how professional training impacts teaching practices. Using a qualitative approach, the research delves into the lived experiences of social studies teachers of Tacurong City Division secondary schools, who have integrated new instructional methods into their classrooms. Participants were selected through purposive sampling and shared insights through interviews. The study highlights three key processes: infusion, where teachers integrate new strategies like technology and differentiated instruction into their curriculum to enhance student engagement; diffusion, which involves sharing these practices among colleagues to foster collaboration and peer mentoring. Acculturation focuses on adapting teaching methods to address students’ cultural and emotional needs, promoting inclusivity and sensitivity. Results indicate that while instructional training significantly enhances teaching strategies, challenges like technological limitations, large class sizes, and financial constraints hinder full implementation. Despite these barriers, the study underscores the transformative potential of instructional training in creating inclusive, dynamic learning environments. Teachers become more adaptable and student-centered, improving both pedagogical effectiveness and student outcomes. Recommendations call for systemic support to address challenges and maximize benefits of instructional training.